Sleep problems and profiles in attention deficit hyperactivity disorder assessed by the Children Sleep Habits Questionnaire-Abbreviated in Colombia (2018)
ABSTRACT: Introduction. Sleep problems are frequent in patients with attention deficit hyperactivity disorder (ADHD), but often underestimated in clinical settings. Objective. To describe the main characteristics of sleep habits in an ADHD outpatient population using the Children Sleep Habits Questionnaire-Abbreviated (CSHQ-A) to compare ADHD groups according to the presence of comorbidity and the presence of current treatment, and to determine sleep profiles by using latent class analysis (LCA). Method. A sample of 228 ADHD patients (Mage = 11.5 years old, (IR = 9 - 15) were enrolled. ADHD comorbidities and treatments were registered. Parents/caregivers filled out the questionnaire. Participants groups were compared, and LCA was used to classify profiles of similar sleep patterns. Results. The ADHD group with treatment had a higher score in the CSHQ-A than the group without treatment. Four classes emerge: Class 1 only children, males, half with comorbid ADHD, many with treatment, and with many sleep problems (CSHQ-A mean: 25.98). Class 2: mostly adolescents, female, with comorbid anxiety disorder, and who did not show sleep problems (CSHQ-A mean: 12.78). Class 3: only adolescents, males, comorbid with major depressive disorder and CSHQ-A who showed many sleep problems. Class 4: only children, males, the majority with treatment, with some sleep problems. Discussion and conclusion. In this ADHD sample, patients with psychopharmacological treatment have a greater report of sleep problems by the CSHQ-A compared to those who do not receive treatment.